On species separation in $n$-component mixture under microgravity - Mojtabi, Mehdi; Charrier-Mojtabi, Marie-Catherine; Mojtabi, Abdelkader (Comptes Rendus. Mécanique)
Recently, we proved that it was possible to significantly increase the importance of the species separation for binary mixtures, under microgravity, using forced convection obtained by a uniform translational displacement of the horizontal isothermal walls of the cell maintained at $T_{h}$ and $T_{c}$ respectively, with $Δ T = T_{h} -T_{c}$.The present work is an extension of the study performed by Mojtabi (2020) with various mixtures, from binary to $n$-component mixtures. An application with a ternary mixture was presented. The mixture of tetralin, isobutyl benzene, $n$-dodecane with respectively 0.8–0.1–0.1 mass fractions was studied experimentally in weightlessness.